Wireless Module for Distance Measurement of Patient’s Temperature in Hospitals - Dimitrov, D. Tz. (Elektronika ir Elektrotechnika, 2008)
System for distance measurements and data collection of patients’ temperature in hospitals is analyzed. Microcontrollers and radiofrequency transmitters are used to implement the described module. The wireless system for temperature data transmission consists of subsystems for the patient and for the physician. The module for remote supervision of the temperature of hospitalized patients facilitates work of medical staff. Ill. 6, bibl. 9 (in English; summaries in English, Russian and Lithuanian).